An Occlusive Syndrome with Dabigatran Overdose - X, Chapalain; L, Bellamy; M, Guillouët; A, Caubel; Y, Ozier; O, Huet (Archives of Clinical and Medical Case Reports, 2019)
Purpose: The aim of this case report is to describe the management of a severe dabigatran overdose in the context of an intestinal obstruction. Clinical Description: Here we report the case of a 75-year-old female patient treated with dabigatran etexilate (150 mg, twice daily), requiring emergency surgery in the context of small bowel occlusion. On admission, the patient presented a severe dabigatran overdose without acute renal insufficiency. The first coagulation test showed a dabigatran concentration of 2,361 ng/ml. Before surgery, three sessions of intermittent hemodialysis (IHD) were performed without ultrafiltration, with a duration of 4 to 8 hours in order to decrease blood concentrations of dabigatran. The surgical procedure, performed by exploratory laparotomy, revealed an occlusion of the small intestine flange. During surgery, no abnormal bleeding occurred. Conclusion: We hypothesized that the occlusive syndrome had probably increased bioavailability of dabigatran leading to overdose. This report confirms efficiency and indication of HDI during dabigatran overdose before emergent surgery.